Development and validation of an ultrahigh performance liquid chromatography‐high resolution tandem mass spectrometry quantification method for hypoglycin A and methylene cyclopropyl acetic acid carnitine in horse serum in cases of atypical myopathy. Issue 5 (12th December 2017) - Rudolph, Wiebke; Remane, Daniela; Wissenbach, Dirk K.; Klein, Carmen; Barnewitz, Dirk; Peters, Frank T.
Abstract: Atypical myopathy (AM) is a fatal disease in horses presumably caused by hypoglycine A (HGA) from ingested maple seeds and its active metabolite methylene cyclopropyl acetic acid (MCPA). The aim of this study was the development and validation of a rapid and simple assay for HGA and MCPA‐carnitine in horse serum and its application to authentic samples. Identification and quantification were carried out by ultra high performance liquid chromatography–high resolution tandem mass spectrometry (UHPLC–HRMS/MS) with full‐scan/data‐dependent MS/MS. Chromatographic separation was performed by isocratic elution on a hydrophilic interaction liquid chromatography (HILIC) column (100 x 2.1 mm, 1.7 μm). Serum samples (250 μL) were worked up by protein precipitation. The method was validated according to international guidelines with respect to selectivity, linearity, accuracy, precision, matrix effects, and recovery. The calibration range was from 100 to 2000 ng/mL for HGA and from 10 to 1000 ng/mL for MCPA‐carnitine. HGA and MCPA‐carnitine showed acceptable accuracy and precision (bias ‐3.0% to 1.1%; RSD 9.2% to 12.4%). The limit of quantification (LOQ) was defined as the lowest calibrator and well below the lowest published serum concentrations in affected horses. Matrix effects ranged from ‐79% to +20% (RSD 4.2% to 14.4%), recoveries from 17.9% to 21.1% (RSD 2.3% to 10.8 %) for low and high quality control samples, respectively. Applicability was tested in 10 authentic AM cases. In all specimens, relevant amounts of HGA and MCPA‐carnitine were found (570–2000 ng/mL; ~8.5–150 ng/mL, respectively). The developed assay allows reliable identification and quantification of HGA and MCPA‐carnitine in horse serum and will be helpful to further study the association between HGA/MCPA and AM. Abstract : Hypoglycine A (HGA), an amino acid present in sycamore maple seeds, is suspected to provoke equine atypical myopathy (AM). The aim of this study was the development of a fast and easy ultra high performance liquid chromatography‐high resolution tandem mass spectrometry method for reliable identification and sensitive quantification of HGA and its metabolites especially methylene cyclopropyl acetic acid carnitine (MCPAC) in horse serum. The fully validated method could be successfully applied to real cases of suspected AM.